2002
DOI: 10.1140/epje/i2002-10026-0
|View full text |Cite
|
Sign up to set email alerts
|

Brownian motion of particles embedded in a solution of giant micelles

Abstract: We have measured the mean-square displacement of colloidal particles embedded in a semi-dilute solution of worm-like micelles, using diffusing wave spectroscopy. This allowed us to describe their rheological properties over a very wide time range. At very short times, the particles diffuse freely in the solvent, and then, they experience the characteristic relaxation times of the living chains. We deduced directly, from the mean-square displacement of the particles, the mechanical properties of the micellar so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 0 publications
5
93
1
Order By: Relevance
“…Experiments using diffusing wave spectroscopy [60,61] and singleparticle tracking [25] revealed that the immersed particles exhibit three distinct diffusive behaviors in different time windows. It was shown that particles surrounded by the micellar network undergo a Brownian diffusion at short (sub-milliseconds) times until they engage with the caging effects of the micellar network, while at later times (milliseconds to sub-seconds) one observes a seemingly confined Brownian motion.…”
Section: B Time-averaged Mean Squared Displacementmentioning
confidence: 99%
“…Experiments using diffusing wave spectroscopy [60,61] and singleparticle tracking [25] revealed that the immersed particles exhibit three distinct diffusive behaviors in different time windows. It was shown that particles surrounded by the micellar network undergo a Brownian diffusion at short (sub-milliseconds) times until they engage with the caging effects of the micellar network, while at later times (milliseconds to sub-seconds) one observes a seemingly confined Brownian motion.…”
Section: B Time-averaged Mean Squared Displacementmentioning
confidence: 99%
“…In the circumstances, the data of MSD in region III (or long t dec ) plays a more significant role in the calculation compared with that in other regions. 28,29,41,42 Solid-liquid balance (SLB) parameter, i.e., the slope of MSD between 2.5 ms and 1.5 s of decorrelation time, characterizes ratio between solid-(SLB=0) and liquid-like (SLB≥1) behaviors of the specimen. [27][28][29][40][41][42] EI, MVI, and SLB are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At intermediate times the MSD increase slows down considerably while at longer times the normal linear increase is reached again. This is a typical behavior of particle probes in worm-like micelle solution [32] [34].…”
Section: Resultsmentioning
confidence: 99%
“…Following the model outlined in Refs [34] [35]. The MSD corrected for multi-exponential relaxation times evolves in time as:…”
Section: Resultsmentioning
confidence: 99%